Opportunities and possibilities for implementing information technologies in physical education and sport in primary education - Alina Petruța Țurcanu; Vizitiu Lakhdari Elena (Editura Univeristatii "Stefan cel Mare" din Suceava, 2024)
With the evolution of technology, its applicability in various fields has brought significant benefits. It is not surprising that the field of physical education and sport has also progressed considerably thanks to technological innovations. The integration of these improvements within physical education has not only provided substantial benefits, but in some cases revolutionized this competitive sector. Influenced by technological, social and cultural changes, the field of education is facing a new dimension dominated by lifelong learning. For specialists in physical education and sport, this trend is also reflected in the need to improve their instructional-educational process. One modern alternative is the use of information technologies to increase the effectiveness of the teaching process.